Effects of thinking aloud on cognitive effort in translation - Sun, Sanjun; Li, Tian; Zhou, Xiaoyan (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This study investigates the effects of thinking aloud on cognitive effort in translation as a function of source-text difficulty level. It does so by considering time on task, duration of different translation phases (i.e., orientation, draft, revision), cognitive effort of processing the source and target texts, and translation quality. Twenty participants took part in an English–Chinese translation experiment, which comprised two matched sessions – translating while thinking aloud and translating silently. Their translation processes were recorded by means of an eye tracker and a key logger. An adapted NASA Task Load Index was employed to elicit their subjective assessments of translation difficulty levels. The quality of their translations was evaluated. The results of the study reveal a number of important effects of thinking aloud on cognitive effort during translation: on translation duration, cognitive effort, the perceived level of difficulty of a translation as measured by NASA-TLX, and on translating easier texts.